Potential Therapeutic Targets and Vaccine Development for SARS-CoV-2/COVID-19 Pandemic Management: A Review on the Recent Update - Anand, Uttpal; Jakhmola, Shweta; Indari, Omkar; Jha, Hem Chandra; Chen, Zhe-Sheng; Tripathi, Vijay; Pérez de la Lastra, José M. (Frontiers in Immunology, 2021)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is a highly pathogenic novel virus that has caused a massive pandemic called coronavirus disease 2019 (COVID-19) worldwide. Wuhan, a city in China became the epicentre of the outbreak of COVID-19 in December 2019. The disease was declared a pandemic globally by the World Health Organization (WHO) on 11 March 2020. SARS-CoV-2 is a beta CoV of the Coronaviridae family which usually causes respiratory symptoms that resemble common cold. Multiple countries have experienced the first and second wave of the disease and scientific experts are consistently working to find answers to several provocative questions, with an aim to find most suitable ways to contain the virus. Furthermore, potential therapeutic strategies and vaccine development for COVID-19 management are also considered. Currently, substantial efforts have been made to develop successful and safe treatments and SARS-CoV-2 vaccines. Some vaccines such as inactivated vaccines, nucleic acid-based, and vector-based vaccines have entered phase 3 clinical trials. Additionally, diverse small molecule drugs, peptides and antibodies are being developed to treat COVID-19. We present here an overview of the anti-CoV therapeutic strategies; including vaccines and other methodologies, designed for prophylaxis and treatment of SARS-CoV-2 infection with the hope that this analysis could help develop novel therapeutic approaches against COVID-19.